Effects of two nights partial sleep deprivation on an evening submaximal weightlifting performance; are 1 h powernaps useful on the day of competition? - Brotherton, E. J.; Moseley, S. E.; Langan-Evans, C.; Pullinger, S. A.; Robertson, C. M.; Burniston, J. G. (Chronobiology International, 2019)
We have investigated the effects that sleep restriction (3-h sleep during two consecutive nights) have on an evening (17:00 h) submaximal weightlifting session; and whether this performance improves following a 1-h post-lunch powernap. Fifteen resistance-trained males participated in this study. Before the experimental protocol commenced, 1RM bench press and inclined leg press and normative habitual sleep were recorded. Participants were familiarised with the testing protocol, then completed three experimental conditions with two nights of prescribed sleep: (i) Normal (N): retire at 23:00 h and wake at 06:30 h, (ii) partial sleep-deprivation (SD): retire at 03:30 h and wake at 06:30 h and (iii) partial sleep-deprivation with nap (SDN): retire at 03:30 h and wake at 06:30 h with a 1-h nap at 13:00 h. Each condition was separated by at least 7 days and the order of administration was randomised and counterbalanced. Rectal (Trec) and mean skin (Ts) temperatures, Profile of Mood Scores, subjective tiredness, alertness and sleepiness values were measured at 08:00, 11:00, 14:00 and 17:00 h on the day of the weightlifting session. Following the final temperature measurements at 17:00 h, participants completed a 5-min active warm-up before a `strength` protocol. Participants performed three repetitions of right-hand grip strength, then three repetitions at each incremental load (40%, 60% and 80% of 1RM) for bench press and inclined leg press, with a 5-min recovery in between each repetition. A linear encoder was attached perpendicular to the movement, to the bar used for the exercises. Average power (AP), average force (AF), peak velocity (PV), distance (D) and time-to-peak velocity (tPV) were measured (MuscleLab software) during the concentric phase of the movements for each lift. Data were analysed using general linear models with repeated measures. The main findings were that SD reduced maximal grip (2.7%), bench press (11.2% AP, 3.3% AF and 9.4% PV) and leg press submaximal values (5.7% AP) with a trend for a reduction in AF (3.3% P = 0.06). Furthermore, RPE increased for measures of grip strength, leg and bench press during SD. Following a 1-h powernap (SDN), values of grip and bench press improved to values similar in N, as did tiredness, alertness and sleepiness. There was a main effect for "load" on the bar for both bench and leg press where AP, AF, tPV values increased with load (P < 0.05) and PV decreased from the lightest to the heaviest load for both bench and leg press. An interaction of "load and condition" was present in leg press only, where the rate of change of AP is greater in the N than SD and SDN conditions. In addition, for PV and tPV the rate of change was greater for SDN than N or SD condition values. In summary, SD had a negative effect on grip strength and some components of bench and inclined leg press. The use of a 1-h power nap that ended 3 h before the "strength" assessment had a positive effect on weightlifting performance, subjective mood and ratings of tiredness.